Many Labs 5: Replication of van Dijk, van Kleef, Steinel, and van Beest (2008). Issue 3 (September 2020) - Skorb, Lauren; Aczel, Balazs; Bakos, Bence E.; Feinberg, Lily; Hałasa, Ewa; Kauff, Mathias; Kovacs, Marton; Krasuska, Karolina; Kuchno, Katarzyna; Manfredi, Dylan; Montealegre, Andres; Pękala, Emilian; et al.
As part of the Many Labs 5 project, we ran a replication of van Dijk, van Kleef, Steinel, and van Beest's (2008) study examining the effect of emotions in negotiations. They reported that when the consequences of rejection were low, subjects offered fewer chips to angry bargaining partners than to happy partners. We ran this replication under three protocols: the protocol used in the Reproducibility Project: Psychology, a revised protocol, and an online protocol. The effect averaged one ninth the size of the originally reported effect and was significant only for the revised protocol. However, the difference between the original and revised protocols was not significant.